N-acetilcisteína bloqueia o desenvolvimento da sensibilização comportamental ao etanol e as alterações na proteína (Delta)FosB - Silva, Gessynger Morais (2016)
Ethanol addiction is a serious public health problem that still needs more effective pharmacological treatment. A key factor in the development and maintenance of this disease is the development of neural plasticity that occurs in the mesocorticolimbic brain pathway upon chronic ethanol abuse. These plasticity events are, in general, maladaptive and affect numerous neurotransmitter systems and intracellular molecules. One of these molecules is ΔFosB, a transcriptional factor that is altered after chronic drug use. Behavioral sensitization is a phenomenon resulting from repeated administration of abuse drugs useful for the study of the neural alterations related to addiction. Recent works have shown a role for the imbalance of glutamatergic neurotransmission in the symptoms found in addicted people. In this line, the treatment with N-acetylcysteine, a L-cysteine prodrug that acts restoring extrasynaptic concentrations of glutamate through the activation of cystine-glutamate antiporter, has shown promising results in the treatment of psychostimulant addiction. Thus, we evaluated the effects of N-acetylcysteine treatment in behavioral and molecular alterations induced by chronic ethanol administration. Swiss mice were subject to thirteen days of daily ethanol administration to induce the development of behavioral sensitization. Two hours before each ethanol administration and locomotor activity assessment, animals received N-acetylcysteine injections i.p.. Right after the last test session, their brains were removed for ΔFosB and cystineglutamate antiporter quantification. We found that N-acetylcysteine treatment blocked ethanol-induced behavioral sensitization, the increase of ΔFosB content in the medial prefrontal cortex and its reduction in the nucleus accumbens. Our results suggest a possible use of N-acetylcysteine in the ethanol-related disorders.